TREATMENT OF CONDYLOMA ACUMINA WITH PODOPHYLLOTOXIN VERSUS COMBINATION THERAPY - Rashid, Abdul; Rehman, Zia -ur-; Xiasheng, Wang (Journal of Ayub Medical College Abbottabad, 1998)
Condyloma acuminata is growing problem due to its resistance to conventional treatment, increased recurrence rate and its relationship with carcinoma. We have designed this study to evaluate the efficacy, adverse effects and immunomadulating effects of podophyllotoxin as a treatment modality of condyloma acuminate as compared to podophyllotoxin plus interferon alpha-1 cream. Podophyllotoxin as monotherapy and its combine1 ion therapy with interferon alpha-1 cream produced complete response in 40% and 68% while recurrence in 48%> and 20% patients respectively. Topical podophyllotoxin produced pain and inflammation while after its combination with interferon alpha-1 cream. The incidence of adverse effects remained the same. Lymphoblast transformation activity and natural Killer activity were performed for every patient before either of treatment modalities and after only in case of combination thereby. KEY WORDS: Condyloma acuminate podophyllotoxin, interferon alpha-1 Lymphoblast transformation activity, Natural Killer activity.